ODI poverty briefing - Overseas Development Institute (London, England) (London Overseas Development Institute, 1998)
The ODI Poverty Briefings series summarised contemporary debate, insights and experience on ways of more effectively reaching and benefiting the poor. They covered new thinking on and recent experience of poverty reduction measures and emerging approaches to poverty alleviation by donor agencies as well as natural resource, finance and trade aspects. The analysis, evidence and insights was drawn from ODI's own recent research and reviews of wider contemporary research, issues being debated and observation from the field
Keywords: Poverty; POVERTY; DEVELOPING COUNTRIES; PERIODICALS